Efficient transduction and optogenetic stimulation of retinal bipolar cells by a synthetic adeno‐associated virus capsid and promoter. Issue 9 (4th August 2014) - Cronin, Therese; Vandenberghe, Luk H; Hantz, Péter; Juttner, Josephine; Reimann, Andreas; Kacsó, Ágota–Enikő; Huckfeldt, Rachel M; Busskamp, Volker; Kohler, Hubertus; Lagali, Pamela S; Roska, Botond; Bennett, Jean
Abstract In this report, we describe the development of a modified adeno‐associated virus (AAV) capsid and promoter for transduction of retinal ON‐bipolar cells. The bipolar cells, which are post‐synaptic to the photoreceptors, are important retinal targets for both basic and preclinical research. In particular, a therapeutic strategy under investigation for advanced forms of blindness involves using optogenetic molecules to render ON‐bipolar cells light‐sensitive. Currently, delivery of adequate levels of gene expression is a limiting step for this approach. The synthetic AAV capsid and promoter described here achieves high level of optogenetic transgene expression in ON‐bipolar cells. This evokes high‐frequency ( 100 Hz) spiking responses in ganglion cells of previously blind, rd1, mice. Our vector is a promising vehicle for further development toward potential clinical use.